REALIZING GENRE PEDAGOGY IN LITERATURE-BASED LESSON PLANS: A QUALITATIVE DOCUMENT ANALYSIS OF EFL PRE-SERVICE TEACHERS AT A PUBLIC UNIVERSITY IN INDONESIA - Riza Amelia (Journal of English and Arabic Language Teaching, 2026)
This study examined how genre pedagogy was realized in literature-based lesson plans developed by EFL pre-service teachers. Employing a qualitative document analysis, the study analyzed five lesson plans collaboratively developed by Semester 6 pre-service teachers enrolled in an English Education program at a public university in Riau, Indonesia. The analysis was guided by the Teaching and Learning Cycle (TLC) proposed by Martin and Rose (2008) and Rose and Martin (2012), focusing on the pedagogical realization of Building Knowledge of the Field, Modelling of the Text, Joint Construction, and Independent Construction. The findings revealed that all lesson plans incorporated the four stages of the TLC, indicating that the participants generally understood the overall instructional sequence of genre pedagogy. The lesson plans were observed to activate prior knowledge, contextualized literary texts, and engaged students in collaborative and independent learning activities. However, the pedagogical purposes of individual stages were realized to varying degrees. For example, explicit genre instruction, teacher-guided joint text construction, and opportunities for independent genre production received comparatively limited attention. These findings suggest that the lesson plans have reflected the Teaching and Learning Cycle (TLC) but only partially realized the pedagogical principles of genre pedagogy. The study contributes to the literature by highlighting teaching and learning cycle aspects of genre pedagogy that may require greater emphasis in preparing EFL pre-service teachers to design literature-based instruction.